Pengaruh Strategi Learning Start With A Question dengan Aplikasi Quizizz terhadap Kemampuan Pemahaman Konsep Matematis dan Kecemasan Matematika Siswa SMP Negeri 2 Bilah Barat - Periyanti Purnamasari Rambe; Lisa Dwi Afri; Suci Dahlya Narpila (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This study was chosen because it is believed to be able to provide a positive impact on the mathematics learning process, especially in improving students' mathematical concept understanding abilities and reducing mathematical anxiety which is often an obstacle in learning. This is to analyze the effect of the Learning Start With A Question (LSQ) strategy with the Quizizz Application on students' mathematical concept understanding abilities and mathematical anxiety at SMP Negeri 2 Bilah Barat. This study used a quasi-experimental design with the Single Group Interrupted Time Series Design approach. The study population was all students of grade VII with a sample of class VII-1 totaling 32 students, selected using the Cluster Random Sampling technique. The results showed that the LSQ strategy with the Quizizz Application had a significant effect on improving students' mathematical concept understanding abilities and reducing students' mathematical anxiety. Based on the hypothesis test using the Paired Sample T-Test, a significance value of 0.001 was obtained, which was smaller than 0.05, so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. This study concludes that the application of LSQ with the Quizizz Application is effective in improving students' mathematical concept understanding and reducing students' mathematical anxiety at SMP Negeri 2 Bilah Barat.